2022
DOI: 10.3390/nano12030463
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Photocatalytic and Photoinduced Antimicrobial Properties of ZnO Thin Films Deposited by HiPIMS through Thermal Oxidation

Abstract: Zinc oxide thin films have been developed through thermal oxidation of Zinc thin films grown by high impulse power magnetron sputtering (HiPIMS). The influence of various sputtering power on thin film structural, morphological, photocatalytic, and antimicrobial properties was investigated. X-ray diffraction (XRD) analysis confirmed that the crystalline phase of ZnO thin films consists of a hexagonal wurtzite structure. Increasing the sputtering power will lead to intrinsic stress on thin films that promote whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 96 publications
1
3
1
Order By: Relevance
“…Moreover, different factors affect antimicrobial efficiency, including the initial amount of bacteria or virus applied on the tested sample, incubation time, temperature, and quantification method. For example, in a previous study, a ZnO deposited sample demonstrated significant inhibition of E. coli and S. aureus, up to 100% [62]. However, the number of bacteria applied on the ZnO samples was 4 × 10 3 CFU/per sample, which is extremely low compared to those used in our study (3.0 × 10 6 CFU/per sample), which made it possible to demonstrate up to a 6 log reduction rate.…”
Section: Discussioncontrasting
confidence: 65%
“…Moreover, different factors affect antimicrobial efficiency, including the initial amount of bacteria or virus applied on the tested sample, incubation time, temperature, and quantification method. For example, in a previous study, a ZnO deposited sample demonstrated significant inhibition of E. coli and S. aureus, up to 100% [62]. However, the number of bacteria applied on the ZnO samples was 4 × 10 3 CFU/per sample, which is extremely low compared to those used in our study (3.0 × 10 6 CFU/per sample), which made it possible to demonstrate up to a 6 log reduction rate.…”
Section: Discussioncontrasting
confidence: 65%
“…The crystallite size effect can also be considered, as it was determined that ZnO:N:F films (Sol 2) have the smallest crystallites (see Table 1). The obtained optical band gaps of sol-gel ZnO and doped ZnO films are in the range of the reported values [8,15,16,19,35,57].…”
Section: Optical Characterizationsupporting
confidence: 57%
“…On the other hand, ZnO:N:F films (Sol 2) possess the lowest E g values except for the value of 300 • C annealed samples. It was previously reported that F doping induces the widening of the optical band gap of the sol-gel ZnO films [35,56]. The increase of the energy gap values of ZnO films with the increase of the fluorine concentration can be attributed to the well-known Burstein-Möss effect.…”
Section: Optical Characterizationmentioning
confidence: 93%
See 1 more Smart Citation
“…In the last decade, the development of nanostructures with various morphologies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] such as: nanowires, nanorods (NR), nanoflowers, nanosheets, nanobelts, nanoneedles, nanoplates, has gained tremendous attention, being used in biological applications [ 8 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]: bioimaging, biosensing, antibacterial and drug delivery agents. In particular, ZnO thin films have optical (photoluminescence) [ 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], electrical (thermoelectric [ 43 , 44 , 45 , 46 ], piezoelectric [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ]) and biological (antimicrobial [ 54 , 55 , 56 ], antibacterial [ 57 , 58 , 59 ]) characteristics, which make them excellent candidates for the development of optoelectronic [ 60 , 61 , 62 , 63 , 64 , 65 ], piezoelectric [ …”
Section: Introductionmentioning
confidence: 99%